Molecular Diagnosis of Duchenne Muscular Dystrophy Using Single NGS‐Based Assay. Issue 2 (7th February 2023) - Nallamilli, Babi Ramesh Reddy; Guruju, Naga; Jump, Vanessa; Liu, Ruby; Hegde, Madhuri
Abstract: Duchenne Muscular Dystrophy (DMD) is an X‐linked inherited neuromuscular disorder caused by pathogenic variants in the dystrophin gene ( DMD ; locus Xp21.2). The variant spectrum of DMD is unique in that 65% of causative mutations are intragenic deletions, with intragenic duplications and point mutations (along with other sequence variants) accounting for 6% to 10% and 30% to 35%, respectively. The traditional strategy for molecular diagnostic testing for DMD involves initial screening for deletions/duplications using microarray‐based comparative genomic hybridization followed by a full‐sequence analysis of DMD for sequence variants. This traditional strategy is expensive and time‐consuming due to the involvement of two separate tests to detect all types of variants in the DMD gene. Recent advancements in next‐generation sequencing (NGS) technology and improvements in analysis algorithms related to copy number variant detection ultimately resulted in the development of a single NGS‐based assay to detect all variant types, including deletions/duplications and sequence variants. This article initially discusses the strategic algorithm for establishing a molecular diagnosis of DMD and later provides detailed molecular diagnostic protocols for DMD, including an NGS‐based sequencing assay with sequence and copy number variant analysis. © 2023 Wiley Periodicals LLC. Basic Protocol : Next‐generation sequencing of the entire genomic sequence of the DMD gene using IDT xGen Lockdown Probes